Perubahan Pengambilan Keputusan Secara Mendalam Mengubah Prinsip Manajemen di Satuan Pendidikan - Suarna, Dedi; Suyatman, Ujang (STIT Fatahillah, 2024)
This study examines how deep decision-making changes can transform the fundamental principles of management within educational institutions. The issue arises from the increasingly complex challenges faced by educational leaders, necessitating a shift in the way decisions are made. The research aims to explore the impact of in-depth decision-making processes on management principles in educational settings. Using a qualitative approach, this study involved interviews and observations with school leaders and administrative staff to gather insights into the evolving decision-making dynamics. The results indicate that adopting a more reflective and comprehensive decision-making process leads to significant shifts in management strategies, fostering more adaptive, inclusive, and participatory leadership practices. The study concludes that by altering decision-making mechanisms, educational institutions can enhance their organizational efficiency and responsiveness to change, ultimately improving the quality of education.